Designing an Information System Architecture for the East Java Community Eye Hospital Pharmacy using TOGAF ADM 9.2 Approach - Hutagalung, Novi Monica; Sudianto, Yupit; Kusumawati, Aris; Fajria, Asruliasani (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The East Java Community Eye Hospital (RSMM Jatim) is a Type B specialty hospital owned by the Provincial Government of East Java. RSMM Jatim envisions becoming a nationally recognized eye hospital. To achieve this vision, one critical requirement is providing high-quality pharmaceutical services. However, the hospital’s pharmacy department currently faces several challenges in supporting its business processes, such as long queues in pharmacy services, inaccuracies in drug inventory data, and lack of system integration. Although RSMM Jatim has implemented the Medify application to manage its Hospital Management Information System (HMIS), its development has not been fully optimized to support all business processes in the pharmacy department. Therefore, this study aims to design an information system architecture using the Enterprise Architecture (EA) approach with The Open Group Architecture Framework (TOGAF) Architecture Development Method (ADM) 9.2. The research focuses on Phase A: Architecture Vision, Phase B: Business Architecture, and Phase C: Information System Architecture. The study involves remapping the pharmacy department's business processes and designing an integrated information system to manage pharmacy queue registration, pharmaceutical supply requests, inventory management, and the handling of expired medications. The research outputs include deliverables for each phase, such as the Principle Catalog, Requirement Catalog, Value Chain Diagram, Functional Decomposition Diagram, Goal/Objective/Requirement, Business Architecture Solutions, Data Entity/Component Catalog, and Application Portfolio Catalog Targeting. This architecture design is expected to serve as a guide for RSMM Jatim in developing an integrated information system for its pharmacy department, ultimately improving service quality and operational efficiency.